2018
DOI: 10.1002/jsfa.9162
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and structural dynamics of the ruminal microbiota in dairy heifers and its relationship to methane production

Abstract: We suggest that Eubacterium and Methanosphaera represent likely targets for CH mitigation efforts in heifers as they were negatively associated with CH production and not significantly associated with production traits. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
(90 reference statements)
0
22
0
Order By: Relevance
“…Both phyla are commonly found in the feces of adult cattle, with Firmicutes commonly being the predominate phylum [6,42]. Most studies of Methanobrevibacter have shown that it is the most common methanogen in the rumen of cattle [43,44], but its role in the fecal microbiota is unclear. Interestingly, reducing this organism could reduce methane production in treated animals and improve feed efficiency [43].…”
Section: Discussionmentioning
confidence: 99%
“…Both phyla are commonly found in the feces of adult cattle, with Firmicutes commonly being the predominate phylum [6,42]. Most studies of Methanobrevibacter have shown that it is the most common methanogen in the rumen of cattle [43,44], but its role in the fecal microbiota is unclear. Interestingly, reducing this organism could reduce methane production in treated animals and improve feed efficiency [43].…”
Section: Discussionmentioning
confidence: 99%
“…As ammonia production in the rumen consumes H 2 gas, Eubacterium spp. might play a role in decreasing CH 4 emissions by depriving methanogens of H 2 [13,48]. The relation between the decreasing amount of GS and the unclassified group belonging to the Saccharibacteria and the YAB-2003 group belonging to the Prevotellaceae is unclear due to the limited knowledge with respect to the physiology of these organisms.…”
Section: Effect Of Diet and Time On Rumen Bacterial Compositionmentioning
confidence: 99%
“…All of them are short chain fatty acids important to the glucose biosynthesis in cattle [2]. Lastly, the family BF16 is also a rumen-native taxon with higher abundance in mature calves and also correlated to methane production [42,43]. All of these taxa were previously reported as members of the regular and efficient microbiota from rumen and their increased abundance may indicate an improved ability to digestion or, at least, a need for more specialized fermentation in rumen due to, for example, more food intake.…”
Section: Discussionmentioning
confidence: 99%